1982
DOI: 10.1295/polymj.14.249
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Solvation of Dextran in Water–Ethanol Mixtures

Abstract: ABSTRACT:The amount of water bound on dextran in water--ethanol mixtures was determined by measuring the adiabatic compressibility of dextran samples of molecular weight above 10 4 • Similar measurements were also carried out on glucose, maltose, and raffinose, and the results were compared with those of dextran. The partial specific compressibility (Kg) of these saccharides increases with increasing ethanol concentration in solvent and takes a constant value above about 20 wt% of ethanol. The interpretation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…• sh , we found for HIC-F1 an intrinsic partial specific adiabatic compressibility k M of 5.4 × 10 −11 cm 3 •g −1 •Pa −1 , then a coefficient of adiabatic compressibility β M of 10.6 × 10 −11 Pa −1 , close to the 12-13 × 10 −11 Pa −1 value found for ice [40,48,[112][113][114]. This value is in the 3-10 × 10 −11 Pa −1 range estimated for dextrans, carageenans, and starch polysaccharides based on volumetric measurements [44][45][46]52], and confirmed the intrinsic rigid nature of highly glycosylated AGPs. For globular proteins, ultrasonic measurements [29,31,36,115,116], and other experimental approaches or molecular dynamic simulations [28,108,[117][118][119][120][121] have provided β M values extrapolated at ambient pressure in the range 10-25 × 10 −11 Pa −1 .…”
supporting
confidence: 75%
See 2 more Smart Citations
“…• sh , we found for HIC-F1 an intrinsic partial specific adiabatic compressibility k M of 5.4 × 10 −11 cm 3 •g −1 •Pa −1 , then a coefficient of adiabatic compressibility β M of 10.6 × 10 −11 Pa −1 , close to the 12-13 × 10 −11 Pa −1 value found for ice [40,48,[112][113][114]. This value is in the 3-10 × 10 −11 Pa −1 range estimated for dextrans, carageenans, and starch polysaccharides based on volumetric measurements [44][45][46]52], and confirmed the intrinsic rigid nature of highly glycosylated AGPs. For globular proteins, ultrasonic measurements [29,31,36,115,116], and other experimental approaches or molecular dynamic simulations [28,108,[117][118][119][120][121] have provided β M values extrapolated at ambient pressure in the range 10-25 × 10 −11 Pa −1 .…”
supporting
confidence: 75%
“…• , and coefficient of partial specific adiabatic compressibility, β s • , indicated that the protein content of AGPs was an important parameter and that hydration of macromolecules (negative values of β s • ) was in absolute value larger than the intrinsic compressibility (flexibility) contribution. In order to get a more general view of the volumetric behavior of AGPs, we then compared it to those of proteins and polysaccharides that we took from the literature [29,32,48,49,52,54,57,86]. Polysaccharides are charged linear polysaccharides salts (K-and Na-carageenans, K-hyaluronate) or branched dextran derivatives (sulfate-, sulfopropyl-and carboxymethyl dextrans) and neutral dextrans (various M w ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 However, little attention has been paid to the role that hydration water has in these systems and its effect in the thermodynamics of complexation. Volumetric and, particularly, compressibility properties of solutes are known to be sensitive to the degree and nature of the solute hydration, and many studies have been carried out on more or less simple compounds containing hydrophobic and hydrophilic groups, such as alcohols, 3 carboxylic acids, 4 carbohydrates, 5 nucleotides, 6 amino acids, 7 etc. In the case of a hydrophobic molecule (e.g., a surfactant) dissolved in water, the solvent reorganizes around it and this results in a negative value of the molar partial adiabatic compressibility.…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in the ethanol concentration, hydration decreases and becomes constant at ca. 20 wt % (7). Bound water of sugars is transferred from solute molecules to solvent by ethanol.…”
Section: Resultsmentioning
confidence: 99%